Australia : Financial Sector Assessment Program; Detailed Assessment of Observance of Standards and Codes. (IMF Staff Country Reports; Country Report ;, 2006)
This assessment of the current state of Australia's implementation of the Basel Core Principles for Effective Banking Supervision has been completed as part of a Financial Sector Assessment Program (FSAP) undertaken in December 2005 by the International Monetary Fund. The assessment team reviewed the legal framework for banking supervision. The team had the benefit of working with a comprehensive self-assessment completed by the Australian authorities, enjoyed excellent cooperation with its counterparts, and received all the information it required. The financial system is relatively large and diversified.